Technology Adoption and Career Concerns: Evidence from the Adoption of Digital Technology in Motion Pictures - Goehring, Grant; Mezzanotti, Filippo; Ravid, S Abraham (The Review of Corporate Finance Studies, 2026)
Abstract This paper studies the impact of career concerns on technological change by analyzing the adoption of digital cinematography in the U.S. motion picture industry. This setting allows us to collect rich data on the adoption of this new technology at the project level (i.e., movie) and on the career of the main decision-maker (i.e., director). We find that early-career directors played a leading role in the adoption of digital technology, an effect that appears to be explained by career concerns, rather than alternative motives we consider and analyze. Technological savviness also plays a role. (JEL: G30, O33, L82, M50)Received: June 25, 2025Editor: J. Anthony Cookson Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.